In Vivo Effects of a Hydroxyapatite-Based Oral Care Gel on the Calcium and Phosphorus Levels of Dental Plaque - Sudradjat, Henny; Meyer, Frederic; Loza, Kateryna; Epple, Matthias; Enax, Joachim (European Journal of Dentistry, 2020)
Objectives Particulate hydroxyapatite (HAP; Ca5(PO4)3(OH)) is a biomimetic oral care ingredient. One mode of action in caries-susceptible individuals may be the adhesion/incorporation of HAP into dental plaque. Therefore, the aim of this in vivo study was to analyze the 3-day effects of a newly developed hydroxyapatite-based oral care gel on the calcium and phosphorus levels within the dental plaque of children.Materials and Methods This study was conducted in Kebon Padangan at Bali in Indonesia. Thirty-four children (mean age, 8.9 years; mean DMF-T [decayed, missing, and filled teeth; permanent teeth], 0.6; mean dmft-t [primary teeth] 4.5) were included in the study. The gel was applied thrice for 3 days by an experienced dentist. Dental plaque was collected at baseline and after the study. Levels of calcium and phosphorus of plaque samples were analyzed by energy-dispersive X-ray spectroscopy.Statistical Analysis Medians for both calcium and phosphorus levels were calculated (baseline and 3-day application of HAP-gel).Results The calcium level increased after 3 days of application of the HAP-gel from 0.25 wt% (median) to 0.40 wt% (median), while the phosphorus level increased from 1.17 wt% (median) to 1.41 wt% (median). However, variations in both calcium and phosphorus levels measured in the pooled dental plaque samples were high.Conclusion Within the limitations of the study, the 3-day application of the oral HAP-gel in children increased the median of both calcium and phosphorus levels in plaque. Consequently, a positive influence on the remineralization/demineralization process is very likely.
Keywords: caries; energy-dispersive X-ray spectroscopy; hydroxyapatite; oral care; dental plaque; calcium and phosphorus levels